The Design and Implementation of a Web-Based Mosque Information System (Case Study at Sirothol Mustaqim Mosque, Manukan) Using Requirement Prototype Approach - Dhany Novaris Maulana; I Gede Wiarta Sena; Alexander Wirapraja (International Journal of Science and Environment (IJSE), 2026)
Mosques play a broad role not only as places of worship, but also as centres for educational, social, and community empowerment activities. However, manual management of mosque activities often leads to problems such as irregular activity schedules, limited information dissemination, and weak communication between administrators and congregations. This study aims to design and develop a web-based Mosque Activity Information System at the Sirothol Mustaqim Manukan Mosque to support more structured, efficient, and integrated management of mosque activities. The development method used is Requirement Prototyping, which consists of ex ante, execution, and expost execution stages, ensuring the system is developed based on user needs. The resultant system efficiently manages data regarding worship schedules, da'wah initiatives, imam and khatib timetables, mosque finances, and administrative documentation, while enhancing communication between administrators and congregants through prompt dissemination of information and activity alerts. The User Acceptance Testing (UAT) results indicated high user acceptance, with all participants rating their experience as either fairly good or very good. Consequently, the developed system is deemed suitable for implementation and has the potential to be applied in the management of mosques with analogous requirements.